Potensi Batuan Induk Batu Serpih dan Batu Lempung di Daerah Watukumpul Pemalang Jawa Tengah - Sachrul Iswahyudi; Asmoro Widagdo (Dinamika Rekayasa, 2009)
Shale and claystone of Watukumpul Area have capability to become the source rock of hydrocarbon because of the ability to conserve the organic material better. Potential of the rock become source rock is depend on its maturity and total organic carbon.This research test eight example of rock to analysis their total organic carbon (TOC) and rock eval pyrolisis. Only one sample is claystone, while the seven others are shales. The analyses provide data of total organic carbon, hydrogen index, and vitrinite reflectances which was used to interpret source rock potential of research area.Through this research is known that the organic material content of shale and claystone of research area own the fair level of total organic carbon. Organic material is included Kerogen Type III with the origin of land organism or plant.These kerogens of research area prefer to produce gas or gas prone. Organic material or kerogens have reached the matured phase to generate hydrocarbon (mature level). Special follow the rock sample came from Location 8 which have over mature level. Its high maturity is suspect have relationship with the intrusion of diorite igneous rock in this research area. Further research is needed to investigate the relationship between diorite intrusion and organic material in this research area.